2010
DOI: 10.1007/s10493-010-9417-1
|View full text |Cite
|
Sign up to set email alerts
|

Ticks on humans in Ankara, Turkey

Abstract: In this study, a total of 5,094 ticks found on humans were examined in terms of species, development stage, gender, host features and seasonality for a year period. Of these ticks 17 were argasid and 5,077 were ixodid. Predominantly species of the ixodid genera Hyalomma, Dermacentor, Rhipicephalus and Haemaphysalis were found on humans in Ankara (Anatolia). Most abundant were Hyalomma nymphs (29.8%) and adults (28.2%). Primary factors in terms of tick bite risk were region, habitat and season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
28
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 14 publications
5
28
1
1
Order By: Relevance
“…It is appears in the present study that tick bites occurred more frequently during the summer seasons when people spend more time in grasslands and picnic sites. This is in agreement with the previous observations (4,12,13,18).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…It is appears in the present study that tick bites occurred more frequently during the summer seasons when people spend more time in grasslands and picnic sites. This is in agreement with the previous observations (4,12,13,18).…”
Section: Discussionsupporting
confidence: 94%
“…Some researchers identified the Hyalomma nymph species as H. aegyptium and the biting ratio was 68.54% in Thrace Province (Tekirdag, Kırıkkale and Edirne) (12) and 52.19% in Istanbul (26). Also Karaer et al (18) were incubated engorged 20 Hyalomma nymphs and all of them were identified as H. aegyptium. In other studies, different tick species were found, the most common species have found as follows: Ixodes nymph and larva (33.62%) in Istanbul (17), H. anatolicum (37.1%) in Sivas (9), Rhipicephalus nymph (42.3%) in Bursa (7) and I. ricinus (50.30%) in Sakarya (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, the most common species was H. marginatum with a rate of 16.82%, showing its feeding preference for humans (Karaer et al, 2011). According to previous studies, Hyalomma, Dermacentor, Rhipicephalus, and Haemaphysalis species constituted the majority of species collected from humans and the field (Aydin and Bakirci, 2007;Karaer et al, 2011). These results are also in accordance with our studies.…”
Section: Discussionsupporting
confidence: 91%
“…parva and Hae. punctata were detected in this study, but Haemaphysalis sulcata was not found; it was previously recorded in low numbers by Karaer et al (2011) in the study area. Haemaphysalis species were collected only in April.…”
Section: Discussioncontrasting
confidence: 73%